STING Operation at the ER/Golgi Interface - Taguchi, Tomohiko; Mukai, Kojiro; Takaya, Eiko; Shindo, Ruri (Frontiers in Immunology, 2021)
DNA is normally present in the nucleus and mitochondria of eukaryotic cells. There are, however, certain instances in which DNA emerges in the cytosol. The cytosolic “self” DNA, leaked out from the nucleus or mitochondria because of the loss of integrity of their membranes, or the cytosolic “non-self” DNA, brought upon infection of DNA viruses, triggers the host immune response. Recent studies have identified two key molecules, cyclic GMP-AMP (cGAMP) synthase (cGAS) and stimulator of interferon genes (STING) in this immune response. STING localizes at the endoplasmic reticulum (ER) and serves as a scaffold for TBK1 kinase, which phosphorylates interferon regulatory factor 3 (IRF3) that induces the type I interferon response. Intriguingly, STING is mobile. After binding of STING to cGAMP, STING immediately exits the ER and translocates to perinuclear compartments that include the Golgi, where STING activates TBK1. In this review, we highlight emerging issues regarding the regulation of STING by membrane traffic, with a particular focus on the retrograde membrane traffic from the Golgi to the ER. The retrograde membrane traffic is recently shown by us and others to be critical for silencing the STING signalling pathway and the defect in this traffic underlies the pathogenesis of the COPA syndrome, a monogenic disorder of immune dysregulation.